Good or Bad Governance for Whom? Governance is a Trojan Horse for Capital Expansion in Pati, Indonesia - Novianto, Arif (Magister Ilmu Administrasi Publik, 2024)
Governance as theory and practice, since the end of the 20th century, has been disseminated as the best form of public management. This notion of governance emphasizes reducing state actor authority, and in the name of participation, the voice of the state actor is positioned on par with the voices of private actors and civil society. To support the concept of governance, international organizations and financial institutions (United Nation, World Bank & IMF) promote the principles of